The relationship between UGT1A1 gene polymorphism and irinotecan effect on extensive-stage small-cell lung cancer - Xiao, Xiao-guang (Onco Targets Ther, 2015)
AIMS: To analyze the distribution of uridine diphosphate glucuronosyltransferase (UGT)1A1 gene polymorphisms in Chinese patients with extensive-stage small-cell lung cancer (E-SCLC), and to evaluate correlations between the UGT1A1 gene polymorphisms and toxicity, and efficacy of irinotecan (CPT-11) based regimen in the patients with E-SCLC. METHODS: The study analyzed the distribution of UGT1A1*28/*6 gene polymorphisms by polymerase chain reaction amplification and pyrosequencing. The analysis of UGT1A1*28 and UGT1A1*6 gene polymorphisms was performed in 67 patients with E-SCLC admitted to the clinic in the Department of Oncology from June 2011 to January 2013. A total of 67 cases with E-SCLC treated with irinotecan (CPT-11)-based regimen were enrolled to observe the adverse events and efficacy during the chemotherapy, including objective response rate, progression-free survival (PFS) and overall survival (OS). The correlation between UGT1A1 gene polymorphisms and severe adverse events was analyzed. The influences of UGT1A1*6/*28 polymorphisms on objective response rate, PFS, and OS were also analyzed. RESULTS: The distribution of UGT1A1 genotypes among 67 patients was as follows: UGT1A1*28 wild-type (WT) genotype TA6/6 (56, 83.6%), heterozygous mutant genotype TA6/7 (11, 16.4%); UGT1A1*6 WT genotype G/G (45, 67.2%), heterozygous mutant genotype G/A (22, 32.8%); no significant difference of PFS and OS was observed between different genotypes. The incidence of grade 3 and 4 delayed diarrhea and neutropenia in the patients carrying UGT1A1*6 G/A mutation was higher than that in the WT genotype (36.4% vs 6.6% P=0.034; 27.2% vs 4.4% P=0.026, respectively). The incidence of grade 3 and 4 thrombocytopenia in the patients carrying UGT1A1*28 TA6/7 mutation was higher than that in the WT genotype (27.2% vs 1.8% P=0.017). The patients simultaneously carrying UGT1A1*28 TA6/7 and UGT1A1*6 G/A mutations were prone to suffering grade 3 and 4 delayed diarrhea and neutropenia. CONCLUSION: For irinotecan-based regimens in E-SCLC, the UGT1A1*28 and UGT1A1*6 locus mutations can be regarded as predictors for severe adverse events. We also found that neither clinical response nor prognosis was significantly associated with the UGT1A1 gene polymorphisms.